An energy efficiency grading system for mobile applications based on usage patterns - Baek, Dusan; Park, Jae Hyeon; Lee, Jung Won (Journal of Supercomputing, 2018)
In selecting a mobile application, the absence of the power-related information obstructs the user from making the smart decision. To handle this problem, we propose an energy efficiency grading system for mobile applications. The system measures the power consumption of the applications over the test scenarios where the representative usage patterns of users are considered. After that, the system rates the grades of the applications based on the measured power consumption. Therefore, the user can refer to the appropriate energy efficiency grade of the applications by taking into account own usage pattern. Moreover, the proposed system provides a label for the energy efficiency grades, so the user can intuitively understand the power-related information of the applications. The evaluation of the system shows that it can help the user to select a better application among interchangeable applications.
Keywords: Energy efficiency grades; Grading system; Low Power; Mobile applications; System rate; Test scenario; Usage patterns; Energy efficiency grade; Low power; Mobile application; Mobile device; Power consumption